2006
DOI: 10.1002/elan.200603537
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids Plasticize and Bring Ion‐Sensing Ability to Polymer Membranes of Selective Electrodes

Abstract: Due to the polymer plasticizing ability and ionic nature of ionic liquids (bistrifluoromethanesulfonimidate salts of 1-butyl-2,3-dimethylimidazolium and dodecylethyldiphenylphosphonium, BDMIm Tf 2 N and DEDPP Tf 2 N, respectively), they were found to be excellent compounds for preparing ion-selective membrane electrodes. Membrane polymers studied were poly(methyl methacrylate) and poly(vinyl chloride). The electrodes demonstrated good and extremely stable response to both cations and anions (including surfacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…Earlier, the capacity of phosphonium-based ILs to plasticize and bring the ion-sensing ability to PVC and PMMA membranes was used for preparing ion-selective electrodes. 115 The PVC-[P6,6,6,14] DCA membranes represented transparent, homogeneous and thin (thickness approximately 10 μm) discs. The color of the membranes was generated during their exposure to the respective metal ion salt solutions (Fig.…”
Section: ·5 Ionic Liquids In Multiple Rolesmentioning
confidence: 99%
“…Earlier, the capacity of phosphonium-based ILs to plasticize and bring the ion-sensing ability to PVC and PMMA membranes was used for preparing ion-selective electrodes. 115 The PVC-[P6,6,6,14] DCA membranes represented transparent, homogeneous and thin (thickness approximately 10 μm) discs. The color of the membranes was generated during their exposure to the respective metal ion salt solutions (Fig.…”
Section: ·5 Ionic Liquids In Multiple Rolesmentioning
confidence: 99%
“…An attractive advantage of ILs is the ability to use them to tailor or tune the properties of a material, such as the solvation environment that determines ion extraction and complexation equilibria within a membrane (85,119). It may be that ILs will replace conventional ion exchangers (119)(120)(121)(122), plasticizers, or even the ionophore in ISEs, but this area seems still in its infancy and only a few examples have been published in the literature (119,120,123,124).…”
Section: Ionic Liquids For Sensing Ionsmentioning
confidence: 99%
“…For example, it was found that imidazolium-based ILs plasticize poly(methyl methacrylate) (PMMA) but not PVC, i.e., membranes plasticized with PVC, are found to be brittle and inductile (120). In addition, it should be noted that ILs influence the fluidity of the membrane, thus determining the diffusion coefficient of the ions and therefore the sensor response time and detection limits (119).…”
Section: Ionic Liquids For Sensing Ionsmentioning
confidence: 99%
“…Several attempts have been made to use ILs as a component of the liquid-membrane ISEs. [12][13][14] In these studies the response of ISEs to the target ions was not nernstian; the slopes less than (RT/z i F)ln 10 were obtained for the plots of the potential against the common logarithm of the concentration of the target ions, where R is the gas constant, T is the absolute temperature, z i is the charge on i in signed units of electronic charge, and F is the Faraday constant. One of the reasons for the non-ideal nernstian response is likely to be the insufficient hydrophobicity of the RTILs added to the membrane.…”
Section: Introductionmentioning
confidence: 99%